KEKERABATAN GENETIK 15 AKSESI PLASMA NUTFAH KARET HASIL EKSPEDISI 1981 BERDASARKAN PENANDA MOLEKULER - Aidi Daslin (AGRIUM: Jurnal Ilmu Pertanian, 2012)
The high genetic variability is important to produced the new improved rubber clones . To get superior progenies can be obtained by crossing between long genetic distance parental.  At the present, rubber clones comes from the genetic materials of Wickham expedition in 1876. To increase the genetic diversity of the rubber, has been carried out expeditions to Brazil through organization of IRRDB ( International Rubber Research and Development Board ) in 1981 . A total of 15 selected accessions of IRRDB materials will be used in breeding programs to assemble the more productive superior clones in the future . Genetic information can be found by using molecular markers by RAPD technique. The purpose of study to determine the genetic distance of 15 germplasm accessions  of the expedition IRRDB 1981 and two clones ( PB 260 and BPM 24 ) as compared of Wickham materials. The results showed there is a 75 % genetic similarity ( 25 % genetic distance ) which have two main groups , namely 10 accessions IRRDB materials divided into four subgroups and 5 accessions of IRRDB with 2 accessions of Wickham in other groups. On genetic similarity coefficient ≥ 95 % , accession PN 5579 has the closest relationship to the materials Wickham ( clone PB 260 and BPM 24 ) , while in IRRDB group are between  the accession PN 5808 with PN 807 , PN 803 with PN 1582, PN 5814 with PN 5819 and PN 5788 with PN 5575 .Keywords:  rubber,  genetic relationship, germplasm, moleculer marker